Clot Structure and Implications for Bleeding and Thrombosis - Mihalko, Emily; Brown, Ashley C. (Seminars in Thrombosis and Hemostasis, 2020)
The formation of a fibrin clot matrix plays a critical role in promoting hemostasis and wound healing. Fibrin dynamics can become disadvantageous in the formation of aberrant thrombus development. Structural characteristics of clots, such as fiber diameter, clot density, stiffness, or permeability, can determine overall clot integrity and functional characteristics that have implications on coagulation and fibrinolysis. This review examines known factors that contribute to changes in clot structure and the presence of structural clot changes in various disease states. These insights provide valuable information in forming therapeutic strategies for disease states where alterations in clot structure are observed. Additionally, the implications of structural changes in clot networks on bleeding and thrombus development in terms of disease states and clinical outcomes are also examined in this review.
Keywords: fibrin; clot structure; atomic force microscopy; fibrinolysis; thrombosis